COMPULSORY ENVIRONMENTAL AUDIT: STUDY OF CASE IN RURAL PROPERTIES OF PARANÁ STATE (BRAZIL) - NOWACKI, Ana Cecilia Bastos Aresta; SILVA, Eduardo Teixeira da; GOBBI, Eduardo Felga; MARÇAL, Caroline Teixeira; PASQUALIN, Luiz Angelo; ALVES, Rafael de Geus (Scientia Agraria, 2009)
The study establishes lines of direction to perform Compulsory Environmental Audit, i.e. legal requirements for rural establishments, in order to allow the application of the State Law n.º13.448/2002 currently in force in Paraná State, that determines the need to evaluate and examine, on a regular and organized basis, the legal, technical, and administrative aspects related to the activities with intensive use of pesticides capable to produce hazardous effects to the environment. It was proposed a specific methodology to conduct the environmental audit in conformity with the rural properties, which involved at first the establishment of the theoretical concepts of the environmental audit, criteria and methodologies of application, then the identification of the environmental aspects of the rural establishments, harmonizing them with the legal criteria to which the rural establishments must attend. Additionally, a specific methodology to audit these establishments for conformity is proposed. The suggested methodology was applied in three rural establishments of Paraná State to validate the lines of direction. It is concluded that the methodology developed and applied in this study enables auditing farms in order to meet the existing state law and that the environmental audit identifies and provides for its own compliance, non-conformities and opportunities for improvement in dealing with environmental issues , allowing to establish the most critical and defining the scale of priorities for resolving problems.